SIFAT ORGANOLEPTIK MI INSTAN TEPUNG UBI JALAR PUTIH PENAMBAHAN TEPUNG DAUN KELOR - M.Anastasia Ari Martiyanti; Vania Vivian Vita (FoodTech: Jurnal Teknologi Pangan, 2018)
Instant noodles are processed flour foods that are often consumed because of their practical processing and presentation. To reduce the use of wheat flour, it is necessary to substitute with other flour which has physical properties and similar nutrient content, one of which is white sweet potato flour. To increase protein and calcium in instant noodles, Moringa leaf flour is added. The purpose of this study was to determine the processing, chemical and sensory characteristics of instant noodles. In this study, instant noodles were made using white sweet potato flour with variations in the addition of Moringa leaf flour, namely 0, 10, and 20 grams. Tests carried out were organoleptic tests (scoring and hedonic tests). Organoleptic test data was processed using ANAVA and if there were significant differences, it was followed by the LSD Test. Scoring test results show that each treatment gives a real difference in the parameters of color, aroma, taste, and texture. The hedonic test results show that the most preferred sample is instant noodles without the addition of Moringa leaf flour which has a color not brownish green, does not smell of Moringa leaves, tasteless taste of Moringa leaves, and a slightly crispy texture. Among the white sweet potato flour instant noodles, the addition of 10 gram Moringa leaf flour with the preferred 20 grams is the addition of 10 grams resulting in a neutral rating scale